Detection of Clonal Relationship Between Carbapenem-resistant Acinetobacter baumannii Isolates in an University Hospital - Kirik, Yasemin; Demirdag, Kutbeddin; Otlu, Baris; Sagmak Tartar, Ayse; Akbulut, Ayhan (Galenos Yayincilik, 2021)
Introduction: Nosocomial infections continue to be an important health problem since they seriously increase the rate of mortality and morbidity as well as hospitalization period and treatment costs. Acinetobacter spp. have an important place among the factors that cause hospital infections. Fast and accurate detection of Acinetobacter baumannii outbreaks is important in the treatment and control of epidemic infections. In our study, it was aimed to investigate the molecular similarities of carbapenem resistant A. baumannii isolates isolated as hospital infectious agents with Pulsed-Field Gel Electrophoresis (PFGE) method. Materials and Methods: This study was conducted in a medical center to examine the genetic relationship of a specific agent group detected in the non-pandemic period and is a cross-sectional study. In our study, the molecular similarities of 93 carbapenem resistant A. baumannii isolates isolated as hospital infectious agents from various clinical materials sent to Firat University Hospital Central Laboratory and Infectious Diseases Department Laboratory between December 1, 2013 and June 30, 2014 were investigated with PFGE method. Results: A. baumannii strains showed 30 different PFGE profiles. Clonally related strains were included in seven different clusters. Eighty of 93 A. baumannii strains in total were included in any cluster. The clustering rate of the strains was found to be 86 %. When the isolate dates of 55 strains in 1 cluster with the highest number of isolates were examined in our study, it was seen that this clone survived in our hospital for about five months. Conclusion: This study showed that A. baumannii strains isolated as nosocomial infection agents can survive for a long time. It was thought that carbapenem resistance spread horizontally among Acinetobacterspp. It was concluded that the necessity of training activities for infection control measures and compliance should be examined, and antibiotic use policies should he revised in terms of carbapenem resistance.
Bir Üniversite Hastanesinde Izole Edilen Karbapenem Dirençli Acinetobacter baumannii Suşlari Arasindaki Klonal Ilişkinin Saptanmasi
Keywords: Acinetobacter baumannii; carbapenem-resistance; PFGE; genotyping